1969
DOI: 10.1002/j.1551-8833.1969.tb03732.x
|View full text |Cite
|
Sign up to set email alerts
|

Taste Quality of Mineralized Water

Abstract: Tests were conducted to determine mineral content levels in drinking water as they affect the taste. Based on test results, a grading schedule is offered which codifies water taste acceptability as a factor of mineral content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

1969
1969
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 6 publications
2
24
0
Order By: Relevance
“…Water for human consumption must be free from organisms and chemical substances in concentration large enough to affect health. ( Bruvold & Ongerth 1969;APHA, 1995;WSC, 2007;Brian 2007) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water for human consumption must be free from organisms and chemical substances in concentration large enough to affect health. ( Bruvold & Ongerth 1969;APHA, 1995;WSC, 2007;Brian 2007) .…”
Section: Introductionmentioning
confidence: 99%
“…(Oteze, 1993) A number of chemical contaminants have been shown to cause adverse health effects in humans as a consequence of prolonged exposure through drinking-water from various sources. (Bruvold & Ongerth 1969;Oteze, 1993;APHA, 1995) The objective of this study is to evaluate some of the parameters that can cause contamination and in what concentration if present and comparing it with set standards of World Health Organization and Standard Organization of Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, electrical conductivity of water is a direct function of its total dissolved salts. Hence it is an index to represent the total concentration of soluble salts in water (Bruvold and Ongerth 1969;Wright et al, 2004). It was observed that chloride value in all the water samples analysed meet the prescribed value of chloride by WHO (2103) and USEPA (2013) for drinking water apart the one from AKWA, IGBELU, OKUSA and IBAKA(well water), GRASLAND borehole, AKUNMI borehole, AAUA sachet, NKAG sachet ABATA and ADEFARATI streams water that were all above the standard values.…”
Section: Fig1mentioning
confidence: 99%
“…A number of chemical contaminants have been shown to cause adverse health effects in humans as a consequence of prolonged exposure through drinking-water from various source much of ill health which affects humanity, especially in the developing countries can be traced to lack of safe and whole some water supply. [2,3] Water for human consumption must be free from living and non-living organisms, toxic elements and chemical substances in concentration large enough to affect health. [4,5].…”
Section: Introductionmentioning
confidence: 99%